Competition for light and water in a coupled soil-plant system. (October 2017) - Manoli, Gabriele; Huang, Cheng-Wei; Bonetti, Sara; Domec, Jean-Christophe; Marani, Marco; Katul, Gabriel
Highlights: A 3D soil-root model is coupled with a 1D plant xylem flow and photosynthesis model. Competition for light and water among multiple trees is investigated numerically. Hydraulic redistribution and canopy shading enhance stand resilience to drought. Equivalent resistor-capacitor models can reasonably describe stand-level dynamics. Abstract: It is generally accepted that resource availability shapes the structure and function of many ecosystems. Within the soil-plant-atmosphere (SPA) system, resource availability fluctuates in space and time whereas access to resources by individuals is further impacted by plant-to-plant competition. Likewise, transport and transformation of resources within an individual plant is governed by numerous interacting biotic and abiotic processes. The work here explores the co-limitations on water losses and carbon uptake within the SPA arising from fluctuating resource availability and competition. In particular, the goal is to unfold the interplay between plant access and competition for water and light, as well as the impact of transport/redistribution processes on leaf-level carbon assimilation and water fluxes within forest stands. A framework is proposed that couples a three-dimensional representation of soil-root exchanges with a one-dimensional description of stem water flow and storage, canopy photosynthesis, and transpiration. The model links soil moisture redistribution, root water uptake, xylem water flow and storage, leaf potential and stomatal conductance as driven by supply and demand for water and carbon. The model is then used to investigate plant drought resilience of overstory-understory trees simultaneously competing for water and light. Simulation results reveal that understory-overstory interactions increase ecosystem resilience to drought (i.e. stand-level carbon assimilation rates and water fluxes can be sustained at lower root-zone soil water potentials). This resilience enhancement originates from reduced transpiration (due to shading) and hydraulic redistribution in soil supporting photosynthesis over prolonged periods of drought. In particular, the presence of different rooting systems generates localized hydraulic redistribution fluxes that sustain understory transpiration through overstory-understory interactions. Such complex SPA dynamics cannot be properly summarized by equivalent ecosystem-scale Resistor-Capacitor (RC) representation. However our results show that, with proper averaging across water flow paths, RC models can provide reasonable estimates of stand-level water and carbon fluxes during inter-storm periods.